Incidental low grade mucinous neoplasm of appendix in pregnancy: A case report & literature review. (November 2020) - Saleem, Nitasha; Shahid, Fakhar; Ali, Syed Mohammed; Rashid, Sameera; Al-Tarakji, Mohannad; Sameer, Mohammad
Abstract: Introduction: Mucinous neoplasms of appendix account for 0.2–0.4% of all the appendix specimens. The occurrence of this neoplasm in pregnancy is extremely rare. We describe a case of a pregnant lady who was diagnosed as acute appendicitis and found to have Low-Grade Mucinous neoplasm on histopathology. In the existent literature, there are only a few such cases reported and none from our Middle East region. Case presentation: 42-year-old pregnant lady at 24 weeks of gestation presented with classical symptoms of acute appendicitis. She had leukocytosis but the Ultrasound was equivocal. She underwent laparoscopic appendectomy and found to have an inflamed appendix. Postoperative recovery was satisfactory and was discharged home. The histopathology report showed low-grade mucinous neoplasm of the appendix and she was detailed about it on follow up. Discussion: The incidence of appendiceal neoplasm is rare in routine appendectomy and carcinoid is the most common tumor of the appendix. Low-Grade mucinous neoplasm is a rare entity and its presence in pregnancy is further rarer. Conclusion: Since this neoplasm does not manifest with a characteristic clinical profile it is difficult to diagnose, even with extensive preoperative evaluation. Although surgical treatment is straight forward, the management of the appendiceal neoplasm during pregnancy necessitates full knowledge of the natural history of the disease to attain equilibrium of concern for maternal survival and fetal health. Highlights: Mucinous neoplasms of appendix are known to be rarely found in all the appendix specimens, but the occurrence of this neoplasm in pregnancy is extremely rare. This neoplasm does not manifest with distinctive clinical profile and it is challenging to diagnose it, even with extensive preoperative evaluation. It is questionable to decide whether to allow pregnancy or terminate unless proper work up is not done to decide the nature of this neoplasm. Further studies dedicated to the understanding of the mucinous neoplasms can help us with designing a more targeted therapeutic plan for such patients.